Long-term Helicobacter pylori infection is associated with an increased risk of carotid plaque formation: a retrospective cohort study - Chen, Yi; Ni, Bingqian; Yang, Chaoyu; Pan, Jingjing; Zhang, Jinshun (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiovascular disease significantly impacts human health. The development of carotid plaques elevates the risk of cardiovascular disease, while the influence of Helicobacter pylori (H. pylori) on carotid plaques remains a subject of debate. This study aimed to investigate the association between H. pylori infection and carotid plaque using a cohort study. Methods The study included individuals who underwent multiple physical examinations at the Health Examination Center of Taizhou Hospital. The relationship between H. pylori and carotid plaque was explored using multifactorial logistic regression analysis. Participants were categorized into groups based on their H. pylori infection status at the initial and final examinations, comprising persistent infection, persistent negative, new infection, and eradication infection, to analyze variations in carotid plaque prevalence among these groups. Results In both univariate and multifactorial regression analyses, H. pylori was identified as a risk factor for carotid plaque development. Moreover, when compared to the persistent negative group, both the new infection and persistent infection groups showed a notable increase in the risk of carotid plaque. Additionally, individuals in the persistent infection group exhibited higher blood pressure and blood glucose levels than those in the persistent negative group. Likewise, there was a discrepancy in the impact of insulin resistance on carotid plaque between the H. pylori positive and negative groups. Conclusion H. pylori is a risk factor for carotid plaque, with a long-term infection associated with an increased risk of carotid plaque formation. In addition, H. pylori promoting carotid plaque formation may be related to blood pressure, blood glucose, and insulin resistance.